A Review and Synthesis of Situational Strength in the Organizational Sciences - Meyer, Rustin D.; Dalal, Reeshad S.; Hermida, Richard (Journal of Management, 2010)
Situational strength pertains to the idea that various characteristics of situations have the ability to restrict the expression and, therefore, the criterion-related validity of individual differences. Despite situational strength’s intuitive appeal, however, little information exists regarding its construct space. This review (a) categorizes extant operationalizations into four facets (constraints, consequences, clarity, and consistency), (b) examines the empirical literature on situational strength—relevant hypotheses, and, on the basis of the proposed taxonomy and literature review, (c) provides several avenues for future theoretical and empirical research. It is the authors’ hope that these efforts will encourage additional research and theorizing on this potentially important psychological construct.